Use of the physical environment to support everyday activities for people with dementia: A systematic review. (July 2018) - Woodbridge, R; Sullivan, MP; Harding, E; Crutch, S; Gilhooly, KJ; Gilhooly, MLM; McIntyre, A; Wilson, L
Difficulty with everyday activities is a key symptom and defining feature of dementia, relating to subjective reports of well-being and overall quality of life. One way to support individuals in their daily activities is by modifying the physical environment to make it easier to interact with during activity performance. This systematic review explores the range of studies available using physical environmental strategies to support performance in everyday activities for people with dementia. Seventy-two relevant studies were identified by the search. Physical environmental strategies included changes to the global environment and to architectural features, use of moveable environmental aids and tailored individual approaches. Strategies supported general everyday activity functioning (N = 19), as well as specific activities, particularly mealtimes (N = 15) and orientation in space (N = 16); however, few studies were found that focused on aspects of personal care such as dressing (N = 1) and showering or the preferred hobbies of individuals (N = 0). Overall, there appeared to be a lack of research within private home environments, and of studies which specify the dementia syndrome or the whole neuropsychological profile of people with dementia. More work is needed to extend theoretical understandings of how people with dementia interact with their environments so that these spaces can be designed to further support activities of daily living performance. Future work in this field could also incorporate the perspectives and preferences of those living with dementia.